PENGARUH ONLINE CUSTOMER REVIEW TERHADAP ONLINE REPURCHASE INTENTION PADA INDUSTRI ONLINE TRAVEL AGENT B2C INDONESIA - Anisa Pujianti, - (2020)
The development of the internet now provides greater opportunities for the service industry in e-commerce, including in the travel industry. Some Indonesian online travel agent companies have succeeded in carrying out strategies that are able to generate intention and attract the attention of consumers to transact, but those that have only received little attention have been acquired by other companies. Online repurchase intentions can be created through online customer reviews. This study aims to determine the effect of online customer review on online repurchase ntentions. The object of this research is online repurchase intention (X) and online customer review (Y). This type of research is descriptive verification. The method used is simple random sampling with a sample size of 200 respondents. The analysis technique used is the analysis of the Structure Equation Model (SEM) using the AMOS 22.0 for Windows program. The findings of this study indicate that online customer review has an influence on online repurchase intention which is in the high category. The dimensions of usefulness of online reviews in online customer reviews contribute greatly to forming online repurchase intentions